Improved methodology for the microwave digestion of carbonate-rich environmental samples. Issue 2 (26th January 2016) - Durand, Axel; Chase, Zanna; Townsend, Ashley T.; Noble, Taryn; Panietz, Emily; Goemann, Karsten
ABSTRACT: Microwave-assisted digestion permits a rapid and total dissolution of sediments and various other sample types, allowing easier and more accurate multi-element determinations. In this study, we present an optimised microwave digestion method for the complete digestion of 200 mg of carbonate-rich sediments. The optimised method prevents the formation of precipitates and assures a complete dissolution of the material. The optimised method involves treatment with concentrated hydrochloric acid (HCl) prior to microwave digestion, which prevents the formation of an insoluble calcium fluoride precipitate associated with the use of hydrofluoric acid (HF). Three different certified reference samples along with a pure calcium carbonate standard and a carbonate-rich in-house marine sediment sample were considered. Sediments were found to only be partially digested if insufficient HF was present, while a noticeable fluoride-based precipitate was found if excess HF was present. Twenty elements were analysed using sector field inductively coupled plasma mass spectrometry (ICP-MS) (Al, Ag, Ba, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Mo, Na, Ni, Sr, Th, Ti, U, V and Zn). A total sample digestion with average elemental recoveries above 90% was obtained by reacting carbonate-rich samples with HCl on a hotplate at 150°C for 2 h (time for the total release of generated CO2 ), prior to any microwave digestion step. This extra step prevented the accumulation of gas in the sealed vessels during digestion, which would otherwise influence the carbonate chemical equilibria and make insoluble calcium available for precipitation. After this initial treatment, the improved digestion method consisted of microwave attack employing a mix of concentrated HCl, nitric acid (HNO3 ) and HF (4 mL/10 mL/2 mL), followed by evaporation on a hotplate. The limits of detection (LOD) obtained using the optimised microwave protocol and ICP-MS measurements were below 0.1 µg/kg for the trace elements and below 0.2 mg/kg for major elements.